The Influence of Perceptions of School Management Training and Work Discipline on Teacher Work Productivity - Lestari, Dessy Ari; Wahyudin, Undang Ruslan; Ismaya, Bambang (Research Horizon, 2025)
This study examines how perceptions of school management training and work discipline influence teacher work productivity. The background highlights that both training and discipline are essential for improving teacher performance but have rarely been studied together in the elementary school setting. The study aims to determine the extent to which these two variables affect productivity. Using a quantitative causal method, data were collected from 178 teachers selected through proportionate stratified random sampling and measured using a Likert-scale questionnaire. Analysis techniques included descriptive statistics, validity and reliability tests, prerequisite tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination. The findings show that 75% of respondents reported that their productivity was influenced by training and discipline. Perceptions of training had a positive and significant effect on productivity (β = 0.421; t = 6.114; p = 0.000), and work discipline also showed a positive and significant effect (β = 0.398; t = 5.772; p = 0.000). Both variables simultaneously demonstrated a significant influence (F = 56.382; p = 0.000), with an R² value of 0.487, indicating that 48.7% of productivity variation is explained by these factors. The study concludes that enhancing school management training and strengthening work discipline are effective strategies for improving teacher work productivity.